DIRECT MAJOR- AND TRACE-ELEMENT ANALYSES OF ROCK VARNISH BY HIGH RESOLUTION LASER ABLATION INDUCTIVELY-COUPLED PLASMA MASS SPECTROMETRY (LA-ICPMS) - Wayne D.M.; Diaz T.A.; Fairhurst R.J.; Orndorff R.L.; Pete D.V. (My University, 2006)
Laser ablation inductively coupled plasma mass spectrometry (LA-ICPMS) was used to determine major and trace element concentrations in rock varnish samples from the Lahontan Range, near Fallon, NV and from a remote wilderness area near the San Juan River, in southeastern Utah. The data indicate that rapid LA-ICPMS analyses provide ample analytical resolution for semi-quantitative compositional determinations of both trace and major elements in the varnish despite the presence of a rock substrate component in most analyses. The overall major element contents of rock varnish from the two localities are grossly similar to rock varnish from other locations analyzed by solution ICPMS, electron microprobe, and energy dispersive scanning electron microscopy (SEM). Differences between microprobe and LA-ICPMS analyses may stem from different sampling scales and different degrees of substrate involvement. It was possible to detect significant variations in trace element contents in the rock varnish samples. The Lahontan Range is situated within a belt of W mineralization, and varnish from that locality contained significantly higher W and Mo contents than varnish from localities outside the W belt. Lead, Tl, Bi, Cd and As contents of varnish-coated pebbles from near the San Juan River in southeastern Utah, varied by an order of magnitude as a function of the position of the sampling site on the pebble. Elevated heavy element contents on the skyward-facing varnish surfaces indicate that heavy elements may be preferentially scavenged at the locations most likely to receive direct inputs of atmospherically-deposited airborne particulates. The source of metal-rich airborne particulates, in this case, is probably any one of several large coal-fired power plants in the Four Corners region, proximal to the San Juan study area. These patterns indicate that rock varnish chemistry is influenced by atmospherically-derived fluxes of both dissolved and particulate constituents, and that rock varnish can be used as a passive environmental indicator for a wide variety of elements, in much the same manner as moss and lichens. © 2006 Elsevier Ltd. All rights reserved.